IDENTIFIKASI POTENSI EKOWISATA DI HUTAN LARANGAN ADAT DESA RUMBIO KEMATAN KAMPAR KABUPATEN KAMPAR - Dicky Zulkarnaen; Defry Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Ecotourism is one form of tourism which is managed by conservation approaches. Ecotourism as part of the concept of tourism development has progressed. with more and more interest in these types of tours based on environmental sustainability. Then in the development of natural tourist destinations obtained reciprocal relationship of mutual benefit between humans as creatures who enjoy nature in its activities with well-preserved nature. This research was conducted in the Hutan Larangan Adat village Rumbio, District Kampar, Province of Riau. This research was carried out for 1 month in November, 2015. Hutan Larangan Adat is a high heritage of indigenous peoples in Rumbio, stored in a variety of natural resources and flora and fauna typical of this area. Geographically situated between 0 ° 56'12 "north latitude and 1 ° 28'17" north latitude, 100 ° 56'10 "east longitude to 101 ° 43'26 '' East Longitude and have an area of approximately 499.30 hectares in 2013. Based on the results of research on the identification of the tourism potential, it can be concluded that the area Hutan Larangan Adat in the village Rumbio very suitable to serve tourist sites include natural attractions like the river which is very clear, fruit trees, plants herbali, large trees are extremely rare in tropical rainforest, see and hear the chirping of various species of birds and other wildlife, as well as historical attractions such as the bulwark against Dutch colonialism.     Keywords: Ecotourism, Hutan larangan adat, Village Rumbio